Hydraulic failure and tree size linked with canopy die-back in eucalypt forest during extreme drought - Nolan, Rachael H.; Gauthey, Alice; Losso, Adriano; Medlyn, Belinda E.; Smith, Rhiannon; Chhajed, Shubham S.; Fuller, Kathryn; Song, Magnolia; Li, Xine; Beaumont, Linda J.; Boer, Matthias M.; Wright, Ian J.; et al. (The New phytologist, 2021)
• Eastern Australia was subject to its hottest and driest year on record in 2019. This extreme drought resulted in massive canopy die-back in eucalypt forests. The role of hydraulic failure and tree size on canopy die-back in three eucalypt tree species during this drought was examined. • Wemeasured pre-dawn and midday leaf water potential (Ψleaf), per cent loss of stem hydraulic conductivity and quantified hydraulic vulnerability to drought-induced xylem embolism. Tree size and tree health was also surveyed. • Trees with most, or all, of their foliage dead exhibited high rates of native embolism (78–100%). This is in contrast to trees with partial canopy die-back (30–70% canopy die-back: 72–78% native embolism), or relatively healthy trees (little evidence of canopy die-back: 25–31% native embolism). Midday Ψleaf was significantly more negative in trees exhibiting partial canopy die-back (−2.7 to −6.3 MPa), compared with relatively healthy trees (−2.1 to −4.5 MPa). In two of the species the majority of individuals showing complete canopy die-back were in the small size classes. • Our results indicate that hydraulic failure is strongly associated with canopy die-back during drought in eucalypt forests. Our study provides valuable field data to help constrain models predicting mortality risk.